Stereotactic radiotherapy in previously treated lung cancers—what are the risks? - Filippi, Andrea Riccardo; Lancia, Andrea; Trovo, Marco (Therapeutic Radiology and Oncology, 2019)
Patients affected by intra-thoracic recurrences of primary or secondary lung malignancies after the first course of definitive radiotherapy (RT) have limited therapeutic options, and they are often treated with palliative intent. Re-irradiation with stereotactic radiotherapy (SRT) represents an appealing approach, due to the optimized dose distribution that allows for high-dose delivery with better sparing of organs at risk; however, toxicity still represents an issue, even with dose-fractionation risk-adapted approaches. This review aims to analyze clinical data and dosimetric parameters related to stereotactic re-irradiation, mainly focusing on the toxicity profile, whose risk often limits the adoption of this technique in clinical practice.